Information-Measuring System for Monitoring the Climate Impact on Overhead Power Lines - Shilin A. N.; Shilin A.A.; Dement’ev S. S. (Problems of the Regional Energetics, 2020)
Studying the problem of diagnosing high-voltage lines is the goal of this research. The high acci-dent rate of overhead lines due to icing and current overloads makes this problem important. Current overloads during distributed power generation lead to overheating of the lines. The goal of the research is achieved due to the fact, that the article notes the relationship between icing and overloads. The necessity of joint solution of these problems and the development of the concept of a multifunctional measuring system is proved. For this, an analysis of the main pa-rameters that determine the mode of operation of overhead lines is carried out. Technical solu-tions for the measurement of these quantities are considered. The detection of ice formation by comparing the values of dew points and desublimation is described. The calculation of the limit-ing current load taking into account weather conditions is given. The amount of sagging wires is selected as a universal characteristic of the state of the line. A significant result of the study is the optical method of icing control. This method consists in measuring the coordinates of the line wires through a weatherproof CCTV-camera. To do this, optical tags and a temperature sen-sor are placed on the wires. The optimal architecture of the measuring system for assessing the climatic impact is given. The significance of the results is that a multifunctional and high-precision system without expensive load sensors is proposed. The conclusion about the im-portance of the results for building a smart grid is made.